Calculation of general parameters for NTRU PRIME UKRAINE of 6-7 levels of stability - Gorbenko, I.D.; Alekseychuk, A.N.; Kachko, O.G.; Yesina, M.V.; Bobukh, V.A.; Kandy, S.O.; Ponomar, V.A. (Radiotekhnika, 2018)
The research was carried out and the development of an effective practical algorithm for the construction of system-wide parameters and keys for cryptographic transformations such as asymmetric ciphers and the key encapsulation protocol was performed. The experimental confirmation of the built-in system-wide parameters and keys of cryptographic transformations such as asymmetric cipher and the key encapsulation protocol of 6 – 7 stability levels based on transformations in the ring of polynomials over the finite fields is presented. The types of attacks that are possible with respect to the specified cryptographic transformations are also presented in this work.